BAKED POTATO: TREN VIRAL DALAM USAHA CAMILAN DI ERA DIGITAL - Talumikir, Samuel Geraldo; Vidyarto Nugroho (Jurnal Serina Abdimas, 2024)
Baked potato has become a viral phenomenon in the snack industry in the digital age, attracting the attention of various demographics, especially the younger generation. This snack offers delicious flavors and ease of preparation, with a variety of toppings that enhance its appeal. The popularity of baked potatoes has surged alongside the influence of social media, which has transformed how people interact with food and discover new snack options. A notable success story is Ben Newman, known as "Spudman," who managed to sell nearly 1,500 potatoes in a single day thanks to viral videos on TikTok. Analysis shows that baked potatoes can serve as a healthier snack alternative, containing beneficial fiber and nutrients, thereby meeting the needs of increasingly health-conscious consumers. Social media acts as a platform that enables entrepreneurs to reach a broader audience, creating strong engagement through visually appealing content. However, consumers must remain discerning when choosing snacks, considering nutritional and caloric aspects. This trend highlights that innovation in presentation and marketing can make simple snacks the center of attention in the food industry. Entrepreneurs are advised to continue innovating and building strong interactions with consumers, as well as providing education about healthy snack choices. With this approach, the presence of baked potatoes can continue to evolve and adapt to the dynamic changes in consumer preferences. ABSTRAK Baked potato, atau kentang panggang, telah menjadi fenomena viral dalam industri camilan di era digital, menarik perhatian berbagai kalangan, terutama generasi muda. Makanan ringan ini menawarkan rasa yang lezat serta kemudahan dalam penyajian, dengan berbagai variasi topping yang menambah daya tariknya. Popularitas baked potato semakin meningkat seiring dengan pengaruh media sosial yang mengubah cara masyarakat berinteraksi dengan makanan dan menemukan pilihan camilan baru. Salah satu contoh sukses adalah Ben Newman, yang dikenal sebagai "Spudman," yang berhasil menjual hampir 1.500 kentang dalam sehari berkat video viral di TikTok. Analisis menunjukkan bahwa baked potato dapat menjadi alternatif camilan yang lebih sehat, mengandung serat dan nutrisi yang bermanfaat, serta memenuhi kebutuhan konsumen yang semakin sadar akan pentingnya pola makan sehat. Media sosial berfungsi sebagai platform yang memungkinkan pelaku usaha untuk menjangkau audiens yang lebih luas, menciptakan keterlibatan yang kuat melalui konten visual menarik. Namun, konsumen perlu tetap bijak dalam memilih camilan, dengan mempertimbangkan aspek nutrisi dan kalori. Tren ini menyoroti bahwa inovasi dalam penyajian dan pemasaran dapat menjadikan camilan sederhana sebagai pusat perhatian dalam industri makanan. Pelaku usaha disarankan untuk terus berinovasi dan menjalin interaksi yang kuat dengan konsumen, serta menyediakan edukasi mengenai pilihan camilan sehat. Dengan pendekatan ini, keberadaan baked potato dapat terus berkembang dan beradaptasi dengan perubahan preferensi konsumen yang dinamis.